2023
DOI: 10.14806/ej.28.0.1027
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Greek Version of Social Appearance Anxiety Scale in Adolescents and Young Adults

Abstract: Many people are worried about their social appearance. The fear of negative evaluation and judgment regarding one’s look in social circumstances is referred to as social appearance anxiety. Social appearance anxiety belongs to social anxiety. The aim of the present study was to validate the Social Appearance Anxiety Scale (SAAS) in the Greek language and to examine its psychometric properties. An online survey was conducted in a Greek population sample of adolescents and young adults aged 18 to 35 years. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The scale has already been translated and cross-culturally adapted for different countries (Hart et al, 2008;Claes et al, 2012;Dakanalis et al, 2016;Radix et al, 2018). In addition, studies have shown adequate psychometric properties of this scale, suggesting its good ability to screen signs and symptoms of social appearance anxiety (Claes et al, 2012;Papapanou et al, 2023). Donofre et al (2021) developed a Portuguese version of the SAAS for the Brazilian context, but its psychometric properties have not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale has already been translated and cross-culturally adapted for different countries (Hart et al, 2008;Claes et al, 2012;Dakanalis et al, 2016;Radix et al, 2018). In addition, studies have shown adequate psychometric properties of this scale, suggesting its good ability to screen signs and symptoms of social appearance anxiety (Claes et al, 2012;Papapanou et al, 2023). Donofre et al (2021) developed a Portuguese version of the SAAS for the Brazilian context, but its psychometric properties have not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between social appearance anxiety and individual characteristics is also relevant to develop appropriate scientific and clinical protocols. Relationships have been found between higher scores of social appearance anxiety and younger age, as well as unemployment (Papapanou et al, 2023). Characteristics such as body mass index and body fat and their relationships with social appearance anxiety have also been studied (Levinson and Rodebaugh, 2011).…”
Section: Introductionmentioning
confidence: 99%